A Century of American Economic Review - Benno Torgler; Marco Piatti (Center for Research in Economics, Management and the Arts (CREMA), 2011)
Using information collected from American Economic Review publications of the last 100 years, we try to provide answers to various questions: Which are the top AER publishing institutions and countries? Which are the top AER papers based on citation success? How frequently is someone able to publish in AER? How equally is citation success distributed? Who are the top AER publishing authors? What is the level of cooperation among the authors? What drives the alphabetical name ordering? What are the individual characteristics of the AER authors, editors, editorial board members, and referees? How frequently do women publish in AER? What is the relationship between academic age, publication performance, and citation success? What are the paper characteristics? What influences the level of technique used in articles? Do connections have an influence on citation success? Who receives awards? Can awards increase the probability of publishing in AER at a later stage?
Keywords: A10; A11; B00; B31; B40; I23; N01; J00; Z00; 330; American Economic Review; publishing economics; rankings; cooperation; authors; editors; board members; referees; connections; awards; paper characteristics; economic history; history of economic thought